Dari Peristiwa ke Struktur: Analisis Iceberg Model dan Theory U atas Pembubaran Retret Cidahu serta Implikasinya terhadap Perlindungan Hukum atas Kebebasan Beragama di Indonesia - Suhendri; Muhammad Hafizh; M. Ainudzaky (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
This article examines the forced dissolution of a Christian youth retreat in Cidahu, Sukabumi, in June 2025 through the Iceberg Model and Theory U, within Indonesia’s constitutional and socio-legal framework on freedom of religion or belief. Using a qualitative library-based socio-legal approach, it draws on constitutional and statutory texts, official human rights reports, selected media coverage, and academic literature on religious conflict, minority rights, and digital intolerance. The study argues that the Cidahu incident was not merely a local disturbance or administrative dispute, but a reflection of deeper structural weaknesses in protecting religious minorities, shaped by legal ambiguity, bureaucratic gatekeeping, majoritarian pressure, and digital amplification. The Iceberg Model reveals layers from visible events to patterns, structures, and mental models of intolerance, while Theory U offers a path toward reflective, rights-based, and inclusive governance